2007
DOI: 10.1108/02635570710740689
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and impacts of ICT investments: perceptions among managers

Abstract: PurposeThe purpose of this paper is to study the characteristics and impacts of information‐communication technology (ICT) investments as perceived by ICT managers.Design/methodology/approachThe paper starts with an overview and a conceptualisation. The empirical part is based on a national RIS 2005 representative telephone survey (n=727) of companies in Slovenia. With respect to ICT developments the Republic of Slovenia, situated between Italy, Austria, Hungary and Croatia, is a typical (median) country of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Fifthly, lack of technology skills in the workforce is a major constraint both on ICT adoption and the exploitation of ICT potential. Managers of small and medium-sized 3PLs must devote more resources to staff training when investing in new ICT systems (Vahovar and Lesjak, 2007).…”
Section: Discussion Of the Main Findings Of The Present Studymentioning
confidence: 99%
“…Fifthly, lack of technology skills in the workforce is a major constraint both on ICT adoption and the exploitation of ICT potential. Managers of small and medium-sized 3PLs must devote more resources to staff training when investing in new ICT systems (Vahovar and Lesjak, 2007).…”
Section: Discussion Of the Main Findings Of The Present Studymentioning
confidence: 99%
“…In fact, perceptual measures have been widely used to assess ICT impacts on firm performance (Ketokivi and Schroeder, 2004;Vehovar and Lesjak, 2007;San-Jose et al, 2009;Campo et al, 2011).…”
Section: Performance Measuresmentioning
confidence: 99%
“…In addition, we have analyzed ICT effects using perceptual measures (Vehovar and Lesjak, 2007;Tallon and Kraemer, 2007;San-Jose et al, 2009) to complement the results obtained in previous quantitative analyses.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, characteristics and impacts of leT investments were researched based on leT managers' perspectives and the outcome revealed that the relative position of leT investments satisfaction is high (Vehovar & Lesjak 2007).…”
Section: Let Investments Impacts On Human Developmentmentioning
confidence: 99%